Ethylene inhibitor, 1-methylcyclopropene, delays macauba fruit ripening and preserves oil quality - Pereira Lopes, Osdneia; Silva de Oliveira, Lucilene; de Melo Goulart, Samuel; Duarte Pimentel, Leonardo; Naomi Kuki, Kacilda; Saraiva Grossi, José Antônio (Revista Ceres, 2026)
The macauba palm produces high-quality oil, with oil content in the fruit potentially increasing after harvest. However, storage limitations due to microorganism and metabolism deterioration restrict the fruit's shelf life. This study evaluated the effects of the ethylene inhibitor 1-MCP on the physiological, physical, and chemical characteristics of macauba palm fruits, focusing on oil quality preservation during storage. Various concentrations of 1-MCP (0, 1000,2000, and 3000 nL L-1) were applied over two exposures (12 and 24 hours) times during fruit storage, assessed at six intervals. Untreated fruits exhibited damaged mesocarpand spoilage by the end of storage, while 1-MCP treatment notably suppressed spoilage. The inhibitor reduced respiration and ethylene production throughout storage, although it did not completely prevent climacteric peaks of CO2 and ethylene, which lessened with higher 1-MCP concentrations. Additionally, 1-MCP delayed ripening, reflected in slower accumulation of total soluble solids and reduced mesocarp firmness loss. Treated fruits showed smaller increases in mesocarp oil content during storage, and the inhibitor also slowed oil acidification. Overall, the responses in all parameters improved with higher 1-MCP concentrations, indicating that 1-MCP could be an effective post-harvest strategy for maintaining the quality of macauba palm fruits and their oil.